Educational Needs on Palliative Care for Cancer Patients in Iran: A SWOT Analysis - Mojgan Ansari; Maryam Rassouli; Mohamad Esmaiel Akbari; Abbas Abbaszadeh; Ali Akbari Sari (International Journal of Community Based Nursing and Midwifery, 2018)
Background: By acceptance of palliative care as a part of health system of each country and due to increasing prevalence of cancer, special focus on stakeholder’s educational needs is of vital importance so that palliative care services are improved and the quality of life of patients is enhanced. This study was conducted to explore the educational needs of stakeholders of palliative care for cancer patients in Iran. Methods: This qualitative study with 20 semi-structured interviews was conducted from August 2016 to February 2017 in Shohadaye Tajrish and Emam Khomeini Hospitals of Tehran. Participants were selected through purposive sampling and included cancer patients and their family caregivers as well as healthcare providers, experts and policy-makers. The data were analyzed through Conventional Content Analysis of Landman and Graneheim using MAXQDA10 software. Statements of each main category of the study were summarized in SWOT categorizes. Result: A total of 546 codes were extracted from the analysis of the interviews and four main categories and four subcategories were identified. The four main identified categories included:”academic education planning”, “workforce education”, “public awareness”, and “patient and caregiver empowerment” that contained our subcategories as follows: “strengths”, “weaknesses”, “opportunities” and “threats” (SWOT). Conclusion: Meeting the educational needs of the stakeholders of palliative care requires policy-makers to identify the factors leading to strategies that are based on the use of opportunities, the removal of weaknesses, and coping with the threats to which the organization is faced.